Breastfeeding in Obese versus Normal-Weight German Mothers of Various Socioeconomic Status. (August 2016) - Grube, Matthias; Keitel-Korndörfer, Anja; Bergmann, Sarah; Wendt, Verena; von Klitzing, Kai; Petroff, David
Background: To a large extent, breastfeeding practices depend on cultural norms. It is thus of particular importance to examine these practices in various settings, especially when considering the effect of complex factors, such as body mass index (BMI) or socioeconomic status. Objective: This study aimed to compare the breastfeeding practices of obese mothers with those of normal weight, taking into account social and economic status. Methods: Obese (BMI ≥ 30 kg/m 2 ) and normal-weight (18.5 kg/m 2 ≤ BMI < 25 kg/m 2 ) mothers with children between the ages of 6 months and 3 years were recruited for this study in Leipzig, Germany, via newspaper ads and other means. Kaplan-Meier curves for portraying breastfeeding over time were analyzed using Cox regression after checking the proportional hazards model. Results: Eighty obese and 70 normal-weight mothers were recruited. Significantly fewer obese mothers breastfed (84%) than normal-weight mothers (96%) (95% confidence interval [CI] for the difference is 3 to 22 percentage points, P = .02). Even after adjusting for the level of education and family income, breastfeeding duration was significantly shorter (2.7 months; 95% CI, 0.8-4.6 months; P = .005) in the obese group than in the normal-weight group. Conclusion: Our findings demonstrate that even at the earliest stages, breastfeeding behavior of obese mothers differs from that of normal-weight mothers.